The Role of Transfer Pricing and Accounting Conservatism on Tax Avoidance: The Moderating Role of Sales Growth - Syawalli, Maharani; Sastri, Enan Trivansyah (Universitas Pamulang, 2025)
This study aims to evaluate and interpret the role of sales growth as a moderating variable and examine how transfer pricing and accounting conservatism influence tax avoidance. A quantitative approach was employed, utilizing secondary data sourced from the annual financial statements of Consumer Non-Cyclical sector companies listed on the Indonesia Stock Exchange (IDX) for the years 2019 to 2023. The research sample included 16 companies, resulting in 80 total observations, which were selected based on purposive sampling criteria. The data were analyzed using Panel Data Regression and Moderated Regression Analysis (MRA), conducted through Eviews 9 and Microsoft Excel. The results of this study indicate that transfer pricing does’nt have a partial effect on tax avoidance, whereas accounting conservatism does have an effect on tax avoidance. In addition, sales growth is not able to moderate the relationship between transfer pricing and tax avoidance, but it can moderate the relationship between accounting conservatism and tax avoidance.